When the night comes falling : a requiem for the Idaho student murders - Blum, Howard (Harper, an imprint of HarperCollinsPublishers, 2024)
"The definitive, inside story of the Idaho murders from bestselling author Howard Blum, whose groundbreaking coverage of the story was nominated for a Pulitzer Prize. Timed for a trial that will capture national attention, When the Night Comes Falling examines the mysterious murders of the four University of Idaho students. Having covered this case from its start, Edgar award winning investigative reporter Howard Blum takes readers behind the scenes of the police manhunt that eventually led to suspected killer, Bryan Christopher Kohberger, and uncovered larger, lurid questions within this unthinkable tragedy. Reminiscent of the panoramic portraiture of In Cold Blood and The Executioner's Song, When the Night Comes Falling offers a suspenseful, richly detailed narrative that will have readers transfixed"--